(untitled) (Research, Society and Development, 2020)
This work presents an analysis and description of an experiment about Hooke’s Law, as a motivating didactic proposal for the learning of Physics, based on the automation of practices through data acquisition using the Arduino prototyping interface. The experiment is presented in detail with its objectives, theoretical basis, list of materials included, assembly scheme, the source code, execution of instructions and data collection. This experiment was applied to a class of students in a high school in the city of Tianguá, in the state of Ceará, called José Ni Moreira, where a possibility of motivating them for physical learning is allowed. An analysis of the results shown that the experimentation strategy in Physics is an important teaching tool and that the articulation between this and the use of plates for prototyping, maximize the development of skills associated with the concepts worked, in such a way that the objectives could be reached, having also, from the analysis, potential to be worked in other school realities.